(3GdaJGhi GdCfbQhjIs - (3GdCfbQhj GdCfchQj, eMeO Hf MSjf, J (B1098 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg cGTa XdGe GdXGde HfhQ GdTQjYI GdeVjFI CeG HYO GdQGLj QMeI QHg eUWai Hf YjSi GdCfbQhj jbhd deG TQYJ HJJHY GdaJGhi GdeYJHQGJ hSejJg eLeY GdefJNH s
(3BNQgG (B:s
(3aEf THg GdYeQ jLH ajg GdOjI hdG jchf GdebJhd Hg TgjOG YfOg hYfOgeG jLH GdbUGU hjchf GdebJhd TgjOG , hGdeSde EPG bJd faSg aj bhd CHj (B" (3M (B" ( (3cPG (B) (3heMeO jZSd hjUdi Ydjgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 246s
(3eYLe GdeDdajf (B3 / 246s
(3NdGUI GdCKQ (B4 / 314s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3Gdabg GdMfHdjs